Preparation and Properties of Poly-2-methacryloyloxyethyl Phosphorylcholine Grafted Silica/Polyethersulfone Composite Membrane - Liang, X.; Qin, L.; Zhang, Y.; Liu, Jian (Jilin Daxue,Jilin University, 2018)
© 2018, Higher Education Press. All right reserved. Zwitterionic 2-methacryloyloxyethyl phosphorylcholine modified SiO2(SiO2-PMPC) was fabricated through reverse atom transfer radical polymerization method(RATRP). Then, SiO2-PMPC/PES composite membranes were prepared using polyethersulfone(PES) as membrane material, via blending-phase inversion method. Morphological structures and properties of the composite membranes were studied by transmission electron microscopy(TEM), scanning electron microscopy(SEM), Fourier transform-infrared spectroscopy(FTIR), X-ray photoelectron spectroscopy(XPS), atomic force microscopy(AFM), contact angle and test membrane performance set-up. The results show that hydrophilicity of the composite membranes increases, with increasing the content of charged zwitterionic materials. The composite membranes present relatively higher rejection of 82.6% to Reactive Black 5 and 92.4% to Reactive Green 19, respectively. However, the retentions of the composite membranes to inorganic salts are less than 8%. The composite membrane can be applied for effectively separating the reactive dyes from the inorganic salts while maintaining high water flux.